2019
DOI: 10.1038/s41598-019-46727-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and 27-hydroxycholesterol promote thyroid carcinoma aggressiveness

Abstract: Cholesterol mediates its proliferative and metastatic effects via the metabolite 27-hydroxycholesterol (27-HC), at least in breast and endometrial cancer. We determined the serum lipoprotein profile, intratumoral cholesterol and 27-HC levels in a cohort of patients with well-differentiated papillary thyroid carcinoma (PTC; low/intermediate and high risk), advanced thyroid cancers (poorly differentiated, PDTC and anaplastic thyroid carcinoma, ATC) and benign thyroid tumors, as well as the expression of genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 61 publications
5
42
3
1
Order By: Relevance
“…27HC is also involved in tumor angiogenesis by inducing VEGF activation through ERa signaling or reactive oxygen species-mediated STAT-3 recruiting (269). Consistently, advanced breast cancers upregulate CYP27A1 while decreasing the expression of CYP7B1, thereby promoting 27HC accumulation (31,270). Higher levels of intracellular cholesterol in cancer cells are determined by aberrant HMGCR activity, due to disrupted sterol-controlled feedback regulation or SREBP-mediated overexpression (271)(272)(273).…”
Section: Oncogenic Signaling and Cholesterol Homeostasismentioning
confidence: 96%
“…27HC is also involved in tumor angiogenesis by inducing VEGF activation through ERa signaling or reactive oxygen species-mediated STAT-3 recruiting (269). Consistently, advanced breast cancers upregulate CYP27A1 while decreasing the expression of CYP7B1, thereby promoting 27HC accumulation (31,270). Higher levels of intracellular cholesterol in cancer cells are determined by aberrant HMGCR activity, due to disrupted sterol-controlled feedback regulation or SREBP-mediated overexpression (271)(272)(273).…”
Section: Oncogenic Signaling and Cholesterol Homeostasismentioning
confidence: 96%
“…CYP7B1 expression has been shown to be lower in ERα-positive breast tumors, relative to normal breast tissue [7], and associated with better prognosis [6,7]. Correlates of tumor protein expression of CYP27A1 and CYP7B1 with cancer characteristics, reproductive and lifestyle factors are not well established in cancer [6,10,11], including breast cancer [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of cholesterol synthesis and steroid levels in different tissues are associated with oxidative stress and cell death, which can contribute to age-related diseases and pathological conditions [5,6]. For example, increased levels of oxysterols have been implicated in Alzheimer's disease (AD), atherosclerosis, type 2 diabetes, and cancer [7][8][9]. In addition, in mice and humans blood steroid concentration changes with age, [10][11][12] and longitudinal studies have identified a correlation between age-related decline in steroid hormones and metabolic syndrome (MetS) as well as cardiovascular disease (CVD) [13,14].…”
Section: Introductionmentioning
confidence: 99%